Impact of trypanosomiasis on male camel infertility - Sara Salah Abdel-Hakeem; Gaber Megahed; Ahmed M. Al-Hakami; Mohammed E. M. Tolba; Yasser F. M. Karar (Frontiers in Veterinary Science)
IntroductionBlood parasitism is a significant clinical disease that silently undermines the livestock industry, particularly affecting camels. This study aimed to assess the prevalence of Trypanosoma evansi in Arabian camels (Camelus dromedarius) and its impact on infertility by examining serum protein fractions, lipids, reproductive indices, and the expression of heat shock protein (HSP70) during breeding season.MethodsA total of 107 male post-pubertal camels, aged between 5 and 10 years, were collected randomly from slaughtering house in Assiut Governorate, Egypt.ResultsMicroscopic and serological examinations revealed that 23.4% (25/107) of the camels were infected with T. evansi. Infected camels exhibited a highly significant increase in total serum protein. The assessment of dyslipidemia, measure as binary variables for lipid profiles (cholesterol, triglycerides, HDL, and LDL), indicated a nonsignificant increase in risk of dyslipidemia in infected camels compared to healthy camels. Proteomic analysis identified four major protein fractions in the infected camels compared to healthy camels with molecular weights of 181.72, 87.59, 30.5, and 19.5 kDa using SDS electrophoresis. Testicular tissue of the infected camels showed degeneration and necrotic changes in seminiferous tubules and interstitial tissue, along with edema and congestion. There was a significant reduction in the diameter of seminiferous tubules and germinal epithelium height. A marked reduction in testosterone levels and a high expression of HSP70 in spermatogonia, spermatocytes, Sertoli cells, and Leydig cells were observed.DiscussionConsequently, a combination of physiological and hormonal analyses may serve as a reliable indicator of Trypanosoma infection.